The Effects of VR Use on Pain Experienced During a Tattoo Procedure: A Pilot Study - Pimentel, Daniel; Kalyanaraman, Sri; Fillingim, Roger; Halan, Shiva (Frontiers in Virtual Reality, 2021)
One of the most socially impactful applications of virtual reality (VR) is its use as a non-pharmacological remedy for both acute and chronic pain. Yet, despite robust findings establishing the analgesic effects of VR, use cases almost exclusively involve (a) patients with acute/chronic pain, which are often difficult to access and vary widely in terms of pain location/severity, or (b) experimentally induced pain, which can have low lab-to-life generalizability. One understudied pain context that may reconcile these limitations is body modification, specifically tattoo procedures. Examining the use of VR during a tattoo offers several benefits to VR and pain research. First, tattoo recipients as a participant pool are more accessible. Second, tattoo pain is presumably more standardized and uniform as it is administered by a machine at a consistent force. Thus, to test these assumptions and expand the scope of VR applications in this domain, we present a mixed-methods investigation testing the effects of VR on pain experienced during a tattoo. Leveraging qualitative interviews with tattoo artists and customers, a 3-month on-site field experiment at a tattoo parlor was conducted. Customers’ self-reported pain ratings (N=16) were collected during 1-hour tattooing sessions and compared between a treatment (VR) and control group. As expected, VR significantly reduced pain ratings during the procedure, and increased pain resilience. By suggesting that the analgesic effects of VR extend to volitional pain during a tattoo, we argue that tattoo pain warrants attention by both VR content developers and researchers interested in studying how immersive content influences real-world pain perception. The study also yields specific guidelines to help designers create and deploy VR experiences for this context. Overall, the results suggest that tattoo sessions present a promising context worthy of further investigation across a variety of VR research programs.